1989
DOI: 10.1111/j.1600-0714.1989.tb00403.x
|View full text |Cite
|
Sign up to set email alerts
|

A highly sensitive method for diagnosis of secondary amyloidosis by labial salivary gland biopsy

Abstract: Both labial salivary gland and gingival biopsies were taken from 19 patients with clinical findings suggestive of secondary amyloidosis. Amyloid deposits were present in all salivary gland biopsies (19/19) while amyloid deposits in gingiva were observed only in three cases (16%). No amyloid was found in similar biopsies from 11 control patients. Periductal amyloid involvement was found along the basement membrane in all salivary gland samples; additionally, 16 cases had periacinar infiltration (84%), 13 had pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
2

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(37 citation statements)
references
References 19 publications
1
34
0
2
Order By: Relevance
“…In a recent report, Delgado and Mosqueda (4) suggested that labial salivary gland (LSG) biopsy was a valuable method for detecting amyloid in patients with type AA amyloidosis. We studied prospectively the value of a combination of Congo red staining and immunohistologic staining, using an antibody directed against serum amyloid P (SAP) component, in detecting amyloid deposits in LSG tissues.…”
mentioning
confidence: 99%
“…In a recent report, Delgado and Mosqueda (4) suggested that labial salivary gland (LSG) biopsy was a valuable method for detecting amyloid in patients with type AA amyloidosis. We studied prospectively the value of a combination of Congo red staining and immunohistologic staining, using an antibody directed against serum amyloid P (SAP) component, in detecting amyloid deposits in LSG tissues.…”
mentioning
confidence: 99%
“…Sampling of gingiva [20,61] and accessory salivary glands [19,20,26,27] do not require special endoscopic equipment, while biopsies from the stomach (Fig. 1), duodenum, colon and rectum do.…”
Section: Electron Microscopymentioning
confidence: 99%
“…Zur Bestimmung der Amyloidablagerung in den Organen wird die Biopsie aus dem entsprechenden Organ empfohlen [4,6]. Alternativ kann auch eine Feinnadelpunktion aus dem subkutanen Fettgewebe oder eine Biopsie der Rektum-und Labienschleimhaut zur Beurteilung der generalisierten Amyloidablagerung vorgenommen werden, wobei in bis zu 80% der Fälle positive Ergebnisse erzielt werden [2]. Mikroskopisch stellt sich Amyloid in der Kongorot-Färbung unter dem Polarisationsmikroskop doppelbrechend dar.…”
Section: Diskussionunclassified